Full chain analysis of nitrogen use efficiency in rice-livestock systems in Uruguay: identifying opportunities for optimizing N management. - Castillo Velazquez, Jesus (Cranfield University, 2022)
Traditionally the rice crop in Uruguay rotates with pastures for direct livestock grazing. This rotation has allowed a constant rice yield increase of 90 kg ha⁻¹ yr⁻¹ over the past 50 years, with yields averaging 8.4 Mg ha⁻¹ in the last decade. Relatively little nitrogen (N) fertilizer is added (80 kg ha⁻¹ yr⁻¹) and the system shows no sign of soil degradation. By contrast, the livestock component is conducted extensively with mostly (75-80%) unimproved pastures, with low animal productivity (100 kg liveweight ha⁻¹ yr⁻¹). This thesis is concerned with how the system N balance is sustained at regional and national scales and if it can be maintained in the future. The objectives were to quantify the N balance (all N inputs – outputs), N surplus (all N inputs – N removed in food products) and N use efficiency (NUE = N in food products / all N inputs) of different rice-livestock- pasture rotations across Uruguay over time. Because historical records of N inputs and outputs are available at regional and national scales, it was possible to assess the whole system in the long term at a farm-gate level. The DNDC model was parameterised with data from a rice long-term experiment and used to compliment the regional N balance data. Results showed a very high average NUE (55–60%) with N balances around neutrality (-6 to +5 kg N ha⁻¹ yr⁻¹) and low N surplus (20 kg N ha⁻¹ yr⁻¹). These values were worse where pastures have been replaced by other cash-crops or rotations shortened. However, there is an opportunity to intensify the system, maintaining the good N balance by improving the livestock component with improved pastures and higher stocking rates to improve N cycling. Results showed the rice-livestock system of Uruguay is a model mixed farming system with several decades of integration.
Haefele, Stephan M. - Associate Supervisor
Keywords: Rice-livestock-pasture rotations; mixed farming systems; nitrogen balance; full chain NUE analysis; Livestock ratios; pasture improvement